A critical study of Amrtacandra's Purusarthasiddhupayah - Mishra, Madhusudan (Punthi-Pustak, 1992)
Critical study of the Puruṣārthasiddhyupāya, Jaina work on the duties of a householder by Amr̥tacandra, 10th cent